The impact of gender-affirming hormone therapy on nutrition-relevant biochemical measures - Waters, Jennifer; Linsenmeyer, Whitney (Frontiers in Nutrition, 2024)
Gender-affirming hormone therapy carries the potential risk for shifts in biochemical markers that may impact cardiometabolic, hematologic, hepatic, and renal health. The critical evaluation of biochemical data is an integral part of a comprehensive nutrition assessment; therefore, nutrition professionals should be aware of shifts that are expected during the course of masculinizing and feminizing hormone therapy. Changes in important biochemical values along with binary sex-specific standards for interpreting laboratory data can pose significant challenges for nutrition professionals working with transgender and gender-diverse patients who receive gender-affirming hormone therapy. Overall, research on the biochemical impact of masculinizing and feminizing hormone therapy is nascent and limited. Methodologies and outcomes measured are heterogenous across studies, introducing complexities that impede researchers from drawing definitive conclusions. In light of these limitations, this narrative review aims to describe the potential implications of masculinizing and feminizing hormone therapy regimens on biochemical measures that may influence nutrition strategies and interventions to promote optimal health.